Modeling the glutamate–glutamine neurotransmitter cycle - Shen, Jun (Frontiers in Neuroenergetics, 2013)
Glutamate is the principal excitatory neurotransmitter in brain. Although it is rapidly synthesized from glucose in neural tissues the biochemical processes for replenishing the neurotransmitter glutamate after glutamate release involve the glutamate-glutamine cycle. Numerous in vivo 13C magnetic resonance spectroscopy experiments since 1994 by different laboratories have consistently concluded: i) the glutamate-glutamine cycle is a major metabolic pathway with a flux rate substantially greater than those suggested by early studies of cell cultures and brain slices; ii) the glutamate-glutamine cycle is coupled to a large portion of the total energy demand of brain function. The dual roles of glutamate as the principal neurotransmitter in the CNS and as a key metabolite linking carbon and nitrogen metabolism make it possible to probe glutamate neurotransmitter cycling using magnetic resonance spectroscopy by measuring the labeling kinetics of glutamate and glutamine. At the same time, comparing to non-amino acid neurotransmitters, the added complexity makes it more challenging to quantitatively separate neurotransmission events from metabolism. Over the past few years our understanding of the neuronal-astroglial two compartment metabolic model of the glutamate-glutamine cycle has been greatly advanced. In particular, the importance of isotopic dilution of glutamine in determining the glutamate-glutamine cycling rate using [1-13C] or [1,6-13C2]glucose has been demonstrated and reproduced by different laboratories. In this article, recent developments in the two-compartment modeling of the glutamate-glutamine cycle are reviewed. In particular, the effects of isotopic dilution of glutamine on various labeling strategies for determining the glutamate-glutamine cycling rate are analyzed. Experimental strategies for measuring the glutamate-glutamine cycling flux that are insensitive to isotopic dilution of glutamine are also suggested.